REPRESENTASI KEARIFAN LOKAL DARI NOVEL KE FILM RAKSASA DARI JOGJA: KAJIAN EKRANISASI - Ajeng Yuditya Siswara; Heru S.P. Saputra; Titik Maslikatin (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2020)
This article analyzes the ecranization pattern between the novel Raksasa Dari Yogya and the adapted film. Filmize novel usually changes the story text's content because not all novel story text content can be moved on the screen. This study aims to get the changes that occur in the novel's adaptation pattern to the form of a film medium, and the shape of representations existed in the two works. This study uses an ecranization perspective. The methodology used in this study is qualitative because the data are in the form of narrative text in novels and visual texts which are the results of the film captured Raksasa Dari Yogya. The data collection method was collected by reading, taking notes, watching, recording film source data, and processing it. Data analysis is in the form of interpretation of data obtained from novel texts and films. The study results show that there are changes: reducing, adding, or varying modifications in terms of the content of the story text. It is caused by the difference between the media used between novels and films. Books and movies reveal Yogyakarta local wisdom representations in the form of arts and tourism. The local wisdom depicted in novels and movies reflects Yogyakarta culture's richness, strengthening a region's identity. The changes can make the film more attractive without changing the substance of the novel as a whole.